Analgesic Activity Of Methanolic Extract Of Jatropha Unicostata Balf, As Endemic Plant In Yemen - MOSA’D AL-SOBARRY,; AHMED ALWASHLI,; YAHIA CHERRAH,; KATIM ALAOUI, (International Journal of Pharma and Bio Sciences, 2011)
In the present study, we evaluate the analgesic activity of methanolic extract obtained from Jatropha unicostata balf leaves, using chemical and thermal models which will induce acute pain in mice and rats. This study was carried out by using sex Swiss mice (20-30gm) and wistar male rats (200-250gm).The methanolic extract was prepared by using maceration at room temperature (25°) over the period of 48 hours. The effect of methanolic extract of Jatropha unicostata was investigated for analgesic activity using acetic acid-induced abdominal writhings (Koster test) and Tail immersion method (Tail flick). The analgesic activity of methanolic extract of Jatropha unicostata at the dose of (100 and 200 mg/kg, p.o.) showed significant (p≤0.001) in reducing abdominal writhings when compared with control and standard drug (Aspirin, 200 mg/kg, p.o.). However this extract at the dose 200 mg/kg, p.o. showed significant (p≤0.001) central analgesic action when compared with control and morphine (5 mg/kg, S.C.) as reference drug. In conclusion, the methanolic extract of Jatropha unicostata balf produced significant analgesic activity in mice and rats.